User Satisfaction Analysis of the Central Lombok Agriculture Website Using EUCS and IPA - Nuri Dinda Lestari; Maulana Ashari; Muhammad Fauzi Zulkarnaen (Jurnal IPTEK Bagi Masyarakat, 2026)
Government agency websites play an important role as a medium for delivering digital-based information and public services. Good website quality will influence the level of user satisfaction as well as the effectiveness of the services provided. This study aims to analyze the level of user satisfaction with the Central Lombok Regency Agriculture Service Website using the End-User Computing Satisfaction (EUCS) method, along with the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) approaches. The research data were obtained through the distribution of questionnaires to 150 respondents using a Likert scale. The analysis results showed that the CSI value was 74.76%, which falls into the satisfied category, indicating that in general the website has been able to meet users’ needs and expectations in providing information and public services. However, the EUCS analysis results indicated that there were still several indicators with relatively lower performance values compared to their level of importance. Furthermore, the IPA mapping results showed that there were no attributes located in Quadrant I, meaning that no main priorities requiring improvement were identified. Attributes in Quadrant II, particularly in the aspects of ease of use and accessibility, demonstrated good performance and should be maintained, while attributes in Quadrants III and IV can serve as evaluation materials in developing the quality of website services. Therefore, continuous evaluation and development are necessary to improve service quality and user satisfaction.